Kepentingan Terbaik Anak dalam Pengaturan Hukum Dispensasi Perkawinan - Kusnadi, Sekaring Ayumeida (Universitas Muhammadiyah Ponorogo, 2025)
The state is constitutionally obligated to ensure the fulfillment of child protection rights as an integral part of human rights. One such regulatory mechanism pertains to the legal framework governing marital agreements, known as marriage dispensation. This legal document is used to deal with specific situations that are considered to be in the best interests of the child. Article 7, paragraph (2) of Law No. 16/2019 on Marriage says that marriage dispensation may be granted in cases of extreme urgency. However, the legal text does not clearly explain what